2021
DOI: 10.3390/cells10030709
|View full text |Cite
|
Sign up to set email alerts
|

Axonal Modulation of Striatal Dopamine Release by Local γ-Aminobutyric Acid (GABA) Signalling

Abstract: Striatal dopamine (DA) release is critical for motivated actions and reinforcement learning, and is locally influenced at the level of DA axons by other striatal neurotransmitters. Here, we review a wealth of historical and more recently refined evidence indicating that DA output is inhibited by striatal γ-aminobutyric acid (GABA) acting via GABAA and GABAB receptors. We review evidence supporting the localisation of GABAA and GABAB receptors to DA axons, as well as the identity of the striatal sources of GABA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 141 publications
(136 reference statements)
0
11
0
Order By: Relevance
“…These data indicate that an adenosine tone preferentially limits DA output during the lower frequencies of DA neuron activity that represent tonic activity, while leaving relatively intact the DA release evoked by the higher frequencies associated with phasic activity in DA neurons. The preferential inhibition of DA release by low frequencies of activity parallels the effects of GABA input to DA axons (Lopes et al, 2019;Roberts et al, 2020;Roberts et al, 2021) and could indicate a preferential influence of striatal adenosine on DA functions that are proposed to be mediated by low frequencies of activity e.g. the ongoing monitoring of reward value and its changes (Wang et al, 2021).…”
Section: A 1 Rs Modify Da Signal Contrast For Firing Frequencymentioning
confidence: 90%
See 1 more Smart Citation
“…These data indicate that an adenosine tone preferentially limits DA output during the lower frequencies of DA neuron activity that represent tonic activity, while leaving relatively intact the DA release evoked by the higher frequencies associated with phasic activity in DA neurons. The preferential inhibition of DA release by low frequencies of activity parallels the effects of GABA input to DA axons (Lopes et al, 2019;Roberts et al, 2020;Roberts et al, 2021) and could indicate a preferential influence of striatal adenosine on DA functions that are proposed to be mediated by low frequencies of activity e.g. the ongoing monitoring of reward value and its changes (Wang et al, 2021).…”
Section: A 1 Rs Modify Da Signal Contrast For Firing Frequencymentioning
confidence: 90%
“…Striatal dopamine (DA) axons are major strategic sites for striatal neuromodulators to influence DA output (Nolan et al, 2020;Rice et al, 2011;Roberts et al, 2021;Sulzer et al, 2016). Adenosine acts at A 1 -and A 2Areceptors on diverse neurons in striatum, and exogenous activation of striatal A 1 -receptors (A 1 Rs) but not A 2receptors inhibits evoked DA release (Okada et al, 1996;O'Neill et al, 2007;O'Connor and O'Neill, 2008;Ross and Venton, 2015).…”
Section: Introduction (638 Words)mentioning
confidence: 99%
“…These data indicate that an adenosine tone preferentially limits DA output during the lower frequencies of DA neuron activity that represent tonic activity, while leaving relatively intact the DA release evoked by the higher frequencies associated with phasic activity in DA neurons. The preferential inhibition of DA release by low frequencies of activity parallels the effects of GABA input to DA axons (Lopes et al, 2019; Roberts et al, 2020; Roberts et al, 2021) and could indicate a preferential influence of striatal adenosine on DA functions that are proposed to be mediated by low frequencies of activity e.g. the ongoing monitoring of reward value and its changes (Wang et al, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…Striatal dopamine (DA) axons are major strategic sites for striatal neuromodulators to influence DA output (Nolan et al, 2020; Rice et al, 2011; Roberts et al, 2021; Sulzer et al, 2016). Adenosine acts at A 1 - and A 2A -receptors on diverse neurons in striatum, and exogenous activation of striatal A 1 -receptors (A 1 Rs) but not A 2 -receptors inhibits evoked DA release (Okada et al, 1996; O’Neill et al, 2007; O’Connor and O’Neill, 2008; Ross and Venton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The VTA and SN in the ventral side of the limbic system have long been considered as the main source of DA transmitters in the cerebral cortex and subcutaneous tissue ( Bjorklund and Dunnett, 2007 ). This area is also involved the processing of reward prediction error calculation ( Schultz et al, 1997 ), with gamma-aminobutyric acid (GABA) in the VTA regulating the amount of reward by inhibiting the activity of DAergic neurons ( Roberts et al, 2021 ), thereby calculating the reward prediction error ( Cohen et al, 2012 ). At the same time, some animal studies have indicated that there are multiple clusters of neurons in this region that are responsible for different motivational functions and may be involved in different neural circuits to process reward and aversive information ( Lammel et al, 2011 ).…”
Section: Neural Network For Dopamine Projectionmentioning
confidence: 99%